A Microrheological Study of Poly(Methyl Methacrylate) Elastomer/Poly(Ethylene Terephthalate) (PMMAelast/PET) Blends - Juciklécia da Silva Reinaldo; Igor Zumba Damasceno; Marcelo Massayoshi Ueki; Edson Noriyuki Ito (Materials Research, 2017)
This study involved an evaluation of the influence of phase inversion in poly(methyl methacrylate) elastomer/poly(ethylene terephthalate) binary blends (PMMAelast/PET) and the effect of the addition of poly(methyl methacrylate-glycidyl methacrylate-ethyl acrylate) (MGE) interfacial compatibilizer on the microrheological properties of this polymer blend. Thermal, dynamic mechanical thermal, rheological and morphological analyses were performed using sensitive techniques such as differential scanning calorimetry (DSC), dynamic mechanical thermal analysis (DMTA), parallel plates rheometry in the linear viscoelastic region, and atomic force microscopy (AFM), respectively. In this study, it was found that variations in the percentage of the PET phase influenced the correlation between the rheological properties at low shear rates and the morphology of the PMMAelast/PET binary blend and of the PMMAelast/PET/MGE compatibilized blend.